Komparasi Biaya Pembibitan Kelapa Sawit (Elaeis guineensis Jacq) Varietas PPKS dan Varietas Damimas Di Pembibitan Kelapa Sawit - Ahmad Fachreza Reza; Nurkhotimah sinaga (Jurnal Ragam Pengabdian, 2026)
This study was motivated by the importance of improving the cost efficiency of oil palm nurseries, as nursery costs directly influence the profitability of plantation companies. The objectives of this study were to determine the nursery cost per seedling of PPKS and Damimas oil palm varieties and to examine whether there were differences in nursery costs between the two varieties. The research was conducted at PT. Abdi Budi Mulia, Teluk Panji Estate, South Labuhanbatu Regency, North Sumatra, Indonesia. A quantitative descriptive approach was employed by analyzing the planned and actual nursery costs during the pre-nursery and main nursery stages. The results showed that the total nursery cost for the PPKS variety was IDR 29,900 per seedling, while the Damimas variety required IDR 32,300 per seedling. The findings indicate that there is a difference in nursery costs between the PPKS and Damimas varieties. The variation in nursery costs was mainly influenced by two factors: the cost of germinated seeds as the initial investment and the success rate of seedling maintenance, as reflected by the thinning-out percentage. These findings provide useful information for plantation companies in selecting oil palm varieties based on nursery cost efficiency.